Photo Catalytic Removal of Paraquat Dichloride Herbicide in Aqueous Solutions by Using TiO2 Nanoparticle - Ayad F. Alkaim (Journal of Global Pharma Technology, 2018)
Abstract In this work treatment of paraquat dichloride herbicide in wastewater using TiO2 nanoparticle as catalyst has been investigated.  Different parameters also investigated such as the effect of catalyst loading, the influence of initial dye concentration, and the effect of intensity of light in order to reach to the optimum operational conditions in which the best treated  of  paraquat dichloride herpicide. The highest removal efficiency of paraquat dichloride herbicide was indicated at 0.17 gm/100cm3 mass of aluminum oxide and 100 ppm of paraquat dichloride herbicide. photocatalytic degradation of paraquat dichloride herbicide was favorable in the 7.33 mW/cm2 light intensity. The percentage efficiency of removal paraquat dichloride herbicide equal 94. 77 %.Keywords: TiO2 nanoparticle, Paraquat dichloride herbicide, Photoefficiency.